From fat to facts: Anthropometric references and centile curves for sum of skinfolds and waist-to-hip ratio in 2,507 adults - Francesco Campa; Giuseppe Coratella; Cristian Petri; Fabrizio Spataro; Davide Charrier; Giuseppe Cerullo; Giulia Baroncini; Eleonora Faraone; Giorgio Pio Alberto Marinelli; Sofia Serafini; Salvatore Vaccaro; Matteo Pincella; et al. (PLoS ONE, 2025)
Background and aims Direct assessment of skinfold thickness and waist and hip girths provides information about body fat and its distribution, avoiding estimation errors due to predictive equations. The present study aimed to provide new centile curves for the sum of eight skinfold thicknesses (Σ8SKF) and waist-to-hip ratio (WHR) in adult population, and to identify breakpoints during adulthood. Methods The present investigation was conceived as a multicenter, cross-sectional study. Stature, body mass, eight skinfold thicknesses (i.e., triceps, biceps, subscapular, iliac crest, supraspinal, abdominal, thigh, and calf) and waist and hip girths were measured according to the International Society for the Advancement of Kinanthropometry protocol in 1,313 men and 1,194 women aged 18–65 years. Smoothed age- and sex-specific percentile curves were generated using the Lambda Mu and Sigma method. For both sexes, simple linear regressions of the dependent variable (Σ8SKF and WHR) versus the explanatory variable (age) were performed to investigate changes in the response variable’s slope and to test for potential breakpoints. Results Reference percentile curves (3rd, 10th, 25th, 50th, 75th, 90th, and 97th) for Σ8SKF and WHR were provided. In men, Σ8SKF increased by 1.0 mm/year between the ages of 21 and 59, while in women, it increased by 3.8 mm/year between the ages of 38.5 and 47. In men, WHR showed a progressive increase of 0.004/year until the age of 28.4, followed by a slower increase of 0.003/year throughout the lifespan. In women, WHR increased by 0.003/year from the age of 20–65. Conclusions Σ8SKF and WHR appear sex- and age-specific. Scientists and practitioners are provided with reference values for the adult population.